Analisis Daya Saing Ekspor Komoditi Kopi (Hs 090111) Indonesia Di Pasar Amerika Serikat : Pendekatan RSCA dan CMS - Fatimah, Nurul; H, Ignatia Martha; Asmara, Kiki (Department of Agribusiness, Halu Oleo University, 2021)
Indonesia is one of the largest coffee exporting countries in the United States market after Brazil, Colombia, Vietnam, and Guatemala. It is still unable to shift the export of coffee commodities from these four countries. This research aims to analyze the competitiveness and performance of coffee exports in the United States market using data analysis methods such as Revealed Symmetric Comparative Advantage (RSCA) and Constant Market Share (CMS). Research is classified as quantitative research that utilizes secondary data, an annual time series data, namely 2010-2019. The data source is exported data for Indonesian coffee commodity digit 6 with HS 090111 (Coffee, not roasted, not decaffeinated) obtained from the International Trade Center (ITC). This study's value results indicate that RSCA Indonesia is 0.87, where the RSCA is> 0. This shows that Indonesia still has competitiveness, although it is lower than Brazil0.95, Colombia, 0.96, and Guatemala, 0.97, and Indonesia is still superior to Vietnam, which is equivalent. 0.79. Meanwhile, the CMS value states that the Indonesian coffee commodity is less desirable in the United States market with an average commodity composition effect value of -0.00006. However, an increase in demand for Indonesian coffee commodities with an average market distribution effect value of 0.00002 and commodity Indonesian coffee has a competitive edge. Strong in the US market with an average competitiveness affect rating of 0.00001.